Access to cochlear implants: Time to reflect. (1st April 2016) - Raine, Christopher; Atkinson, Helen; Strachan, David R.; Martin, Jane M.
Abstract : Cochlear implant (CI) intervention is expensive and accessed mainly by developed countries. The introduction of Universal Newborn Hearing Screening and funding via a public health service give children better access to CIs. However for adults large disparities exist between utilization and estimated prevalence. In the UK CI selection criteria are restrictive compared with many other countries. Improved audiological awareness and screening programmes for adults would improve access to hearing technologies that would improve health and quality of life. Hearing loss itself has significant medical and financial burdens on society and by investing in early intervention and using best technology this would mitigate some of the rising associated medical costs.